Hypersensitivity to Hydroxyl Radicals in Rat Basilar Artery After Subarachnoid Hemorrhage - Tsuyoshi Nishihashi; Cristina C. Trandafir; Aimin Wang; Xu Ji; Yoshiharu Shimizu; Kazuyoshi Kurahashi (Elsevier, 2006)
Abstract.: Vasospasm after subarachnoid hemorrhage (SAH) is a serious complication and we have been investigating the relationship between vasoconstrictors and vasospasm after SAH. The present study was designed to investigate the vasocontractile responses to reactive oxygen species in isolated rat basilar arteries from the control and experimental SAH rats. Contractile responses to hydroxyl radicals in basilar arteries from SAH rats were 3 - 6-fold higher than those in control rats. The present results clearly indicate that hypersensitivity to hydroxyl radicals may contribute to the vasospasm after SAH. Keywords:: subarachnoid hemorrhage, hydroxyl radical, rat basilar artery